Aesthetic Values of Jordanian Digital Painting - jaradat , Moath Abdallah mohammad; Jamali, Siti Salmi Binti; Husain , Adzira Binti (Journal of Ecohumanism, 2025)
This study seeks to examine the aesthetic values ​​in Jordanian digital painting, specifically how it contributes to the production of digital artworks that interact with the artist's cultural reality and social issues.. The study sample consisted of five Jordanian artists from the last decade of the twentieth century, who were selected through the snowball method. The research used a qualitative approach that combines semi-structured interviews and content analysis. The study found that the aesthetic values ​​in Jordanian digital painting branch out and intersect with each other to form the aesthetics of the painting, through several values ​​that revolve around (expressive values, artistic values, creative values). Each of them was an integral part of the perfection of the aesthetic structure of the painting and its deep meanings. In terms of artistic practices, Jordanian artists used advanced tools and programs, with Adobe Photoshop and Illustrator being the most common, to produce, process, and print their digital artworks. Farther more, We conclude that open culture, global cultural transformations, their direct and indirect influences, and the state of global cultures and politics have led to a shift in the concept of painting among Jordanian artists. As a result, their work has transitioned from traditional to digital forms. This evolution has coincided with changes in the cultural references of the artists, where contemporary digital technology has played a significant role in producing artworks with aesthetic values in a modern digital style.